Protein DEK and DTA Aptamers: Insight Into the Interaction Mechanisms and the Computational Aptamer Design - Dai, Lijun; Zhang, Jiangnan; Wang, Xiaonan; Yang, Xiaoyue; Pan, Feng; Yang, Longhua; Zhao, Yongxing (Frontiers in Molecular Biosciences, 2022)
By blocking the DEK protein, DEK-targeted aptamers (DTAs) can reduce the formation of neutrophil extracellular traps (NETs) to reveal a strong anti-inflammatory efficacy in rheumatoid arthritis. However, the poor stability of DTA has greatly limited its clinical application. Thus, in order to design an aptamer with better stability, DTA was modified by methoxy groups (DTA_OMe) and then the exact DEK–DTA interaction mechanisms were explored through theoretical calculations. The corresponding 2′-OCH3-modified nucleotide force field was established and the molecular dynamics (MD) simulations were performed. It was proved that the 2′-OCH3-modification could definitely enhance the stability of DTA on the premise of comparative affinity. Furthermore, the electrostatic interaction contributed the most to the binding of DEK–DTA, which was the primary interaction to maintain stability, in addition to the non-specific interactions between positively-charged residues (e.g., Lys and Arg) of DEK and the negatively-charged phosphate backbone of aptamers. The H-bond network analysis reminded that eight bases could be mutated to probably enhance the affinity of DTA_OMe. Therein, replacing the 29th base from cytosine to thymine of DTA_OMe was theoretically confirmed to be with the best affinity and even better stability. These research studies imply to be a promising new aptamer design strategy for the treatment of inflammatory arthritis.